Penn State Then and Now - Little, Pat, 1953-, author 647350 (Lemont : Pat Little Photography, 1999)
Time teaches us appreciation of the past. In this book we examine Penn State's past and compare it with the present. Pat Little, using a process he discovered, takes you on a fascinating journey with an incredibly accurate perspective through old and new photographs. Penn State has gone through many changes. This book will take you to those places that have disappeared and those we still appreciate. Sprinkled throughout are gems of historic information that glide the reader through history and inform us of little known facts. This is an historical treasure all Penn Staters will enjoy.